Intraosseous vs. intravenous access in out-of-hospital cardiac arrest: a systematic review and meta-analysis of clinical outcomes - Emmanuel Kokori; Nawaf Al-Hashemi; Ziad Sad Aldeen; Ravi Patel; Nicholas Aderinto; Gbolahan Olatunji; Iyanuloluwa S. Ojo; Israel Charles Abraham; Hafeez Shaka (International Journal of Emergency Medicine)
Abstract Background Out-of-hospital cardiac arrest (OHCA) is a critical emergency with low survival rates despite advancements in prehospital care. Timely vascular access for medication administration is essential, with intravenous (IV) and intraosseous (IO) access as primary strategies. While IO offers rapid and reliable access under challenging conditions, its effectiveness compared to IV access remains uncertain. This systematic review and meta-analysis evaluate the comparative outcomes of IO versus IV access in OHCA. Methods A systematic search of PubMed, Embase, SCOPUS, and other databases was conducted up to November 2024, following PRISMA guidelines. Studies were included comparing IO and IV access in OHCA and reporting outcomes such as return of spontaneous circulation (ROSC), 30-day survival, and neurological outcomes. Meta-analyses were performed using random-effects models to calculate pooled odds ratios (ORs) and mean differences. Heterogeneity was assessed using the I² statistic, and sensitivity analyses were conducted to evaluate the robustness. Results Nineteen studies involving ~ 140,000 observations (7 randomized controlled trials, 12 retrospective/observational) were analyzed. IO access was associated with significantly lower odds of ROSC (OR 0.75, 95% CI 0.65–0.85, p = 0.0003; 17 studies) and FNO at hospital discharge (OR 0.53, 95% CI 0.35–0.80, p = 0.0058; 12 studies) compared to IV access. The 30-day survival showed a non-significant trend favoring IV access (OR 0.59, 95% CI 0.28–1.21, p = 0.1088; 5 studies). Subgroup analyses revealed stronger IV advantages for shorter emergency medical services (EMS) response times (< 10 min; FNO: OR 0.55, ROSC: OR 0.75) and shockable rhythms (FNO: OR 0.53, ROSC: OR 0.75). Conclusion While IO access is a viable alternative when IV access is challenging, this study highlights its association with poorer survival and neurological outcomes in OHCA. The findings show the importance of prioritizing IV access. Further high-quality research is needed to refine recommendations for OHCA management.